Implementering av kognitiv ergonomi inom primärvården: Minska kognitiv belastning genom trådlös kommunikation - Asadi, Romina; Lehrberg, Sophie (My University, 2021)
This is a bachelor’s thesis done at the Department of Industrial and Materials Science at Chalmers University of Technology, in the spring of 2021 in collaboration with the Västra Götaland region's primary care department, Närhälsan. The purpose and goal of the project has been to treat cognitive load affecting healthcare staff, and thus develop a product that can reduce this load. The work was based on three problemscenarios that emerged from communication with the client, as well as two former master's students whose master's thesis we went over. These scenarios were triage, lab and staff coordination. In order to choose a scenario, the work began with thorough studies in the form of a literature review, and then continued with observations and interviews within a number of groups of staff. Some of the more prominent problems that emerged were high pressure due to shortage of time and many patients, distractions, lack of communication between work groups and uncertainty about where colleagues were. After further analysis of the working groups and the problemareas, the decision was made to focus on developing a solution primarily aimed at the second problem scenario; the lab. The lab staff is responsible for ensuring that operating rooms, among other rooms, are cleaned and ready for the next patient. There were, however, problems in the communication about when cleaning and care of these rooms would take place, which could mainly lead to stress for the lab staff. With this as a starting point, a number of concepts were developed and then evaluated. The project eventually resulted in Locare, consisting of the two components Locare Switch and Locare Map. Locare's function is to communicate to the lab staff when there is a need for cleaning in the rooms the lab staff is responsible for. A solution like Locare is the beginning of the ongoing work to incorporate cognitive ergonomics in healthcare. An improved cognitive environment would not only lead to a less stressed staff, but also a more prosperous and focused staff. The result of this is that their work gets the best conditions, which in the end will benefit the healthcare as well as the patient and their safety.
Keywords: Cognitive ergonomics, Primary care, Medical harm, Patient safety, Human Factors